Empowerment of Persons with Disabilities based on Sharia Economics: Lessons from the Phenomenon of Equality and Social Justice in Indonesia - Nuryanto, Uli Wildan; Yusuf, Furtasan Ali; Junedi, Beni; Pratiwi, Ika; Basrowi; Utami, Pertiwi (Asian Journal of Multidisciplinary Studies, 2024)
Islam has a positive view of the rights of people with disabilities and provides support in efforts to realize equality and social justice for them. On the other hand, people with disabilities are underrepresented in achieving equality and social justice. Thus, the issues that occur in Indonesia have given rise to several perceptions related to the problem of discrimination, the difficulty of fulfilling the rights of people with disabilities, and the accessibility of various sectors that are important to them. Therefore, it is important for a systematic literature review to investigate the picture of equality and social justice for people with disabilities in Indonesia as well as empowerment efforts that can be carried out through the Sharia economic empowerment model proposed by various previous studies. The findings reveal two important things. First, opportunities for equality and social justice for people with disabilities are carried out through some regulations, policies, and superior programs to achieve inclusion in Indonesia. The government is continuing to strive for it, however, it is facing several big challenges that must be immediately resolved. Second, empowering people with disabilities using the Sharia economic empowerment model focuses on two important things, namely changing mindsets and adjusting infrastructure. The conclusion is that Sharia economic empowerment has a great opportunity to realize equality and social justice for people with disabilities in Indonesia. It is hoped that this study can become reference material for community empowerment programs aimed at people with disabilities. Apart from that, it is hoped that it can provide enlightenment regarding changes in people's mindsets and foster participation and self-sufficiency in the community and government in terms of funding sources in the future.